Different effects of exposure to penconazole and its enantiomers on hepatic glycolipid metabolism of male mice. (February 2020) - Meng, Zhiyuan; Liu, Li; Xi, Yexun; Jia, Ming; Yan, Sen; Tian, Sinuo; Sun, Wei; Zhu, Wentao; Li, Xuefeng; Zhou, Zhiqiang
Abstract: (±) - PEN is a chiral fungicide widely used to control powdery mildew in agriculture. Currently, only a few studies have investigated the toxic effects of (±) – penconazole ((±) – PEN) on non-target organisms, and whether (±) - PEN from the enantiomeric level have toxic effects remains unclear. In this study, we systematically evaluated the effects of exposure to (±) – PEN, (+) – PEN and (−) – PEN on liver function in mice. Biochemical and histopathological analyses showed that exposure to (±) – PEN and (−) – PEN led to significant liver damage and inflammation. However, exposure to (+) – PEN treatment did not cause no adverse effects on liver function and inflammation. 1 H-NMR-based metabolomics revealed that exposure to (±) – PEN, (+) – PEN and (−) – PEN led to the animals developing liver metabolic disorder that was caused by changes in glycolipid metabolism. Quantitative analysis of genes regulating glycolipid metabolism revealed that expression of gluconeogenesis and glycolytic pathway genes were altered in individuals exposed to (±) – PEN, (+) – PEN and (−) – PEN. We also found that (±) – PEN, (+) – PEN and (−) – PEN have different effects on lipid metabolism of the liver. Exposure to (±) – PEN and (−) – PEN resulted in significant accumulation of lipids by regulating fatty acid synthesis, triglyceride synthesis, and fatty acid β oxidation pathways. In summary, we found different toxicological effects in individuals exposed to (±) – PEN, (+) – PEN and (−) – PEN. The results of this study are important for assessing the potential health risks of (±) – PEN. Graphical abstract: Image 1 Highlights: Exposure to (±) – PEN and its enantiomers caused hepatic glycolipid metabolism disorder of mice. Both (±) – PEN and (-) – PEN exposures resulted in significant accumulation of lipids. Gluconeogenesis and glycolytic pathways were significantly interfered with (±) – PEN and its enantiomers exposure. Abstract : Different toxicological effects on hepatic glycolipid metabolism were produced with (±) – PEN, (+) – PEN and (−) – PEN exposure.